2021
DOI: 10.3390/antibiotics10101169
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutations Associated with Streptomycin Resistance in Multidrug-Resistant Mycobacterium tuberculosis in Zambia

Abstract: Streptomycin (STR) is recommended for the management of multidrug-resistant tuberculosis (MDR-TB). Streptomycin resistance-conferring mutation types and frequency are shown to be influenced by genotypes of circulating strains in a population. This study aimed to characterize the mutations in MDR-TB isolates and examine their relationship with the genotypes in Zambia. A total of 138 MDR-TB isolates stored at the University Teaching Hospital Tuberculosis Reference Laboratory in Zambia were analyzed using spoligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Phenotypic streptomycin resistance is explained by mutations in rpsL, rrs , and gidB . 13 In the present study, we found that the common mutations that conferred resistance to streptomycin were rpsL K43R and rrs A514C, excluding gidB , similar to that reported previously. 13 Phenotypic resistance to second-line injectables (amikacin, kanamycin, and capreomycin) can be caused by mutations in the rrs gene, tlyA gene, and eis promoter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Phenotypic streptomycin resistance is explained by mutations in rpsL, rrs , and gidB . 13 In the present study, we found that the common mutations that conferred resistance to streptomycin were rpsL K43R and rrs A514C, excluding gidB , similar to that reported previously. 13 Phenotypic resistance to second-line injectables (amikacin, kanamycin, and capreomycin) can be caused by mutations in the rrs gene, tlyA gene, and eis promoter.…”
Section: Discussionsupporting
confidence: 91%
“… 13 In the present study, we found that the common mutations that conferred resistance to streptomycin were rpsL K43R and rrs A514C, excluding gidB , similar to that reported previously. 13 Phenotypic resistance to second-line injectables (amikacin, kanamycin, and capreomycin) can be caused by mutations in the rrs gene, tlyA gene, and eis promoter. 24 In the present study, among the two second-line injectable-resistant M. tuberculosis strains, only one strain (strain 86) had mutation A1401G in rrs , whereas the other did not, suggesting that this mutation may not be enough to explain phenotypic resistance to second-line injectables.…”
Section: Discussionsupporting
confidence: 91%
“…Mutations in embB 306, which is associated with the majority of drug-resistant strains to ethambutol, have also been detected in susceptible strains [ 31 ], whilst the same discrepancy for streptomycin might be due to low-level resistance-conferring mutations in gid to the drug, which may result in susceptible phenotype [ 33 ]. Mutations in rrs and rpsL genes have been associated with intermediate to high [ 34 ] and high levels of resistance to streptomycin [ 33 , 34 , 35 , 36 ], respectively. In addition, drug susceptibility testing is not routinely performed on all patients with TB, hence the treatment regimen in some cases may not be appropriate and this facilitates resistance amplification and further transmission of primary drug-resistant TB [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23,40 The following mutations confer resistance to STR, rpsL (Lys43Arg, Lys88Gln, Lys88Arg, Cys117Thr), rrs (Cys517Thr, Ala514Cys, Ala906Gly, Ala907Cys), gidB (Ala183Val, Gly71Arg, Tyr22His, Gly37Arg, Pro75Ser, Gly76Asp, Ile81Thr, Phe100Leu, Val124Gly, Ala134Gly, Ala138Pro, Ser149Arg, Leu152Ser, and Gly157Arg). 57 Mutations in the rpsL and rrs genes are the major mechanisms that confer resistance to STR in M. tuberculosis, they account for 60-70% of resistance to STR. 29 Recent studies have revealed that mutations in the gidB gene cause low-level resistance and accounts for 33% of resistance to STR in clinical M. tuberculosis isolates.…”
Section: Drug Target Genes and Mutations Conferring Resistance To Str...mentioning
confidence: 99%